Factors that influence job satisfaction among employess / Alia Suaida Mohamad - Mohamad, Alia Suaida (Faculty of Business and Management, 2019)
The purpose of conducting this study is to determine the factor that can influence job satisfaction. The dependent variable for this study is job satisfaction and the independent variable for this study is working hours, job security & safety, relationship with co-worker and top management. This study is aim to determine whether there is a relationship between job satisfaction and all the independent variable. The focus on this study is on the employee who is currently working at Sen Heng warehouse in Shah Alam. A total of 70 questionnaires has been distributed to the employee and the researcher has collected back the questionnaires completely. The data that has been collected will be analyze by SPSS software used to test whether there is a relationship between dependent variable (job satisfaction) and independent variable (working hours, job security & safety, relationship with co-worker and top management). As conclusion, only two independent variables which the hypothesis were supported and have a relationship with job satisfaction. Both two variables are working hours and top management. On the last chapter, there will be providing with findings, discussion, recommendation and conclusion